PDF UJI EFEKTIVITAS EKSTRAK TANAMAN AKAR KUNING (Arcangelisia flava Merr) UNTUK PENGOBATAN PENYAKIT EDWARDSIELLOSIS PADA IKAN LELE (Clarias batrachus) The Effectiveness Test of Yellow Root Plant Extract (Arcangelisia flava Merr) in Treating Edwardsiellosis Di: Maryani Staf Pengajar Program Studi Budidaya Perairan Jurusan Perikanan Fakultas Pertanian Universitas Palangkaraya - journal journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTThis study aims to determine the effectiveness of the use of yellow root plant extract (Arcangelisia flavaMerr) in treating edwardsiellosis disease in catfish (Clarias batrachus). The method used in thisresearch is experimental method complete Randomized Design (RAL) with three treatments and threereplications. The treatments were extract of Yellow Root plants (Arcangelisia flava Merr.) With dose of50 ppm (treatment A), dose 100 ppm (treatment B) and dose 150 ppm (treatment C). The parametersobserved were the change of clinical symptoms, the percentage of test fish recovery rate, and thesurvival of the test fish as well as the water quality. The results showed that the use of yellow root plantextract through immersion in treatment C (dose 150 ppm) is the best treatment with the percentage offish recovery rate of 85.00% and survival rate of test fish is 93.33%. Thus the Yellow Root plant extract(Arcangelisia flava Merr) effective in the treatment of edwardsiellosis disease in catfish (Clariasbatrachus) with recommended dosage is 150 ppm.Keywords: Arcangelisia flava Merr, edwardsiellosis, catfish